Implementasi Metode Double Diamond Design Process pada UI/UX Aplikasi Manajemen Kesehatan dan Gizi Personal (WellFits) - Fatimah, Fitri Asri Nur; Voutama, Apriade (MEANS (Media Informasi Analisa dan Sistem), 2025)
WellFits is an innovative digital solution for personal health and nutrition management, focusing on calorie deficit, stunting prevention in pregnant women, and nutrition consultation with experts. This study applies the Double Diamond Design Process to identify user needs and develop relevant features. The development process includes problem exploration, needs definition, solution development, and implementation with iterative eval_uation based on user feedback. Usability testing results showed an average score of 8.04 out of 10, indicating high satisfaction and ease of use. With features for tracking nutritional intake and expert consultations.